A method for preparing poplar-based porous carbon material by carbonizing solid raw materials

Through the DC arc method and the salt template two-step method, a poplar-based layered porous carbon material was prepared, which solved the problem that traditional methods were difficult to obtain high-performance wood-based carbon materials, achieved the high specific surface area and excellent pore structure of the material, and improved its electrical performance in the field of energy storage.

CN119490177BActive Publication Date: 2025-04-11BEIHUA UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510082036.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-11
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

Traditional preparation methods are difficult to obtain wood-based carbon materials with high specific surface area, high conductivity and rich porosity, which limits its application in the field of energy storage.

Method used

The DC arc method combined with the salt template two-step method is used to pre-treat the poplar chips with arc discharge, and then calcined at high temperature to prepare a poplar-based layered porous carbon material.

Benefits of technology

The high specific surface area of ​​the material and excellent pore structure are achieved, which improves its electrical performance in the field of energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490177B_ABST
    Figure CN119490177B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a poplar-based porous carbon material by carbonizing solid raw materials, and belongs to the field of technology and application of preparing nanomaterials by direct current arc method. The method adopts a direct current arc device, uses a poplar wood chip as an anode, and a high-purity tungsten rod as a cathode, and a carbonization reaction occurs in an inert gas environment to prepare a poplar-based porous carbon material. The present invention adopts a direct current arc method to precisely adjust the reaction conditions during the synthesis process, reasonably regulate the pore structure of the carbon nanomaterial, and achieve performance improvement of the wood-based porous carbon material. The preparation method mentioned in the present invention is simple and efficient, the raw materials are cheap and easy to obtain, the preparation process is simple, the material morphology and internal structure can be precisely regulated, and the product is eco-friendly and pollution-free, providing a new path for the preparation of carbon nanomaterials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparing carbon nanomaterials by a direct current arc method, and relates to a method for preparing a poplar-based porous carbon material by carbonizing solid raw materials. Background Art

[0002] Carbon materials obtained by traditional preparation methods (such as hydrothermal method and activation method) cannot meet the standards of ideal electrode materials such as high specific surface area, high conductivity, and rich porosity. For example, wood-based carbon materials have a small specific surface area, dense structure, and single pores, which are not conducive to high-speed storage and transmission of ions. Hydrothermal carbon materials have a small specific surface area, clogged pores, and underdeveloped porosity, and often require the use of other means to improve material performance. Although the activation method is often used to increase the specific surface area of ​​carbon materials and adjust the pore structure, the excessive use of chemicals will pollute water sources and harm the environment, and it is not in line with the core concept of green energy. Moreover, most of the wood-based carbon materials obtained by traditional preparation methods have the problems of small specific surface area and low rate performance. The defects of the above preparation methods have greatly limited the application of wood-based carbon materials in the field of energy storage.

[0003] Therefore, developing green and efficient preparation methods, exploring green, economical, simple and efficient synthesis methods suitable for different precursors, and further improving the energy storage performance of wood-based carbon materials are the current research hotspots in the field of energy storage.

[0004] As a stable form of gas discharge, arc discharge is generated and maintained independently of ionization conditions and only requires the application of external voltage. In the more than 100 years since the first discovery of arc discharge, people have never stopped paying attention to and exploring arc discharge. Arc discharge methods include DC arc method and AC arc method. The use of DC discharge method to prepare new carbon nanomaterials has a long history. It was first used to prepare carbon nanotubes and has now become one of the most commonly used methods for preparing nanocarbon particles. The general preparation principle is: a certain amount of inert gas, such as Ar, N is filled into a vacuum reaction chamber. 2 , H 2 / Ar, etc., the experimental preparation parameters are gas type, gas pressure, discharge voltage, current, reaction time, etc.; the cathode is generally a high-purity graphite rod (carbon rod is generally used to prepare metal / carbon nanocomposite powder) or a high-melting-point tungsten rod, and the anode is a carbon-nitrogen material (should be conductive so that arc discharge can be generated); the ultra-high temperature zone generated during the arc discharge process (the arc temperature during the discharge process is as high as 3000-3700 °C) causes the anode as a raw material to be continuously evaporated, consumed and decomposed, and the sample preparation is completed under the joint action of multiple factors. In general, researchers often improve the yield of products and prepare new carbon materials by changing the anode raw materials, discharge environment, and air intake methods. In addition, compared with other preparation methods, the DC arc method has the advantages of simpler and more convenient operation, high material yield and large output, and high material universality. And compared with most chemical synthesis methods, the DC arc method does not need to add other auxiliary raw materials (such as activators, catalysts, etc.), which avoids the mixing of impurity elements and affects the purity of the material. It also greatly shortens the preparation time and eliminates the repeated cleaning of samples. What is more noteworthy is that the high temperature and high pressure environment generated when using the DC arc method to prepare carbon materials can achieve material carbonization in a short time, and the obtained carbon nanostructures often have excellent thermal stability.

[0005] However, up to now, there are still few reports on the application of DC arc method in the preparation of biomass materials, especially wood materials. Summary of the invention

[0006] In view of the characteristics of the DC arc method, such as short preparation cycle, environmental friendliness, and simple operation, the present invention proposes a method for preparing poplar-based hierarchical porous carbon materials by combining arc discharge pretreatment with a salt template two-step method for treating carbonized wood. The raw materials are widely available, the synthesis process is green and environmentally friendly, and the preparation method is highly universal. The present invention combines the DC arc method with biomass materials, providing a new idea and new path for developing a simple, efficient, low-cost, and highly universal material synthesis method.

[0007] The present invention provides a method for preparing a poplar-based porous carbon material by carbonizing solid raw materials. The method adopts a direct current arc device, uses a poplar wood chip as an anode, and a high-purity tungsten rod as a cathode, and a carbonization reaction occurs in an inert gas environment to prepare the poplar-based porous carbon material.

[0008] Furthermore, the method comprises the following steps:

[0009] (1) Pretreatment of poplar wood chips by direct current arc method: Poplar wood chips are used as anodes and high-purity tungsten rods are used as cathodes in a direct current arc device. After the reaction chamber of the arc device is in a vacuum state, an inert gas is filled in as the working gas, the power is turned on and the arc is started. During the reaction, the current and the distance between the two electrodes are regulated. After the reaction is completed, the power is turned off. After the temperature inside the reaction chamber cools to room temperature, a passivation gas is introduced for passivation treatment to obtain arc carbonized poplar wood chips.

[0010] (2) High-temperature calcination: The arc carbonized poplar wood chips prepared in step (1) are placed in a tubular furnace for calcination to obtain a poplar-based porous carbon material.

[0011] Preferably, in step (1), the raw material poplar wood chips are first immersed in water for 1 to 5 hours to ensure that the water fills the interior of the wood chips and improves their conductivity, and then they are placed in a DC arc device as an anode.

[0012] Preferably, in step (1), the arc reaction conditions are: prepare the poplar wood chips into a block of 2×2×0.2 cm, the inter-electrode distance is 1-10 mm, the discharge current is 10-70 A, the arc discharge time is 5-40 s, the inert gas is high-purity argon, and the filling pressure is 40-80 KPa. As a key parameter for arc preparation, a moderate inter-electrode distance facilitates the contact of the positive and negative electrodes to start the arc, and timely adjustment of the inter-electrode distance after arc starting is conducive to arc stabilization. Adjusting the discharge current and discharge time can avoid the instantaneous discharge high temperature generated by the arc under high current, which causes the anode material to be ablated and pierced, and can ensure the integrity of the material morphology. A moderate inert gas pressure is conducive to the inert gas always filling the DC arc reaction chamber during the arc reaction process to ensure the normal arc reaction.

[0013] Preferably, in step (1), the passivation gas is a single high-purity argon gas, and the passivation time is 5 to 7 hours.

[0014] Preferably, in step (2), the calcination temperature is 800°C and the calcination time is 100-150 min.

[0015] The present invention also provides a poplar-based porous carbon material prepared by the method, the specific surface area of ​​which is up to 708 m 2 g -1 The mesopore volume accounts for 57.07% of the maximum, and the micropore volume accounts for 42.93% of the maximum.

[0016] The present invention also provides application of the poplar-based porous carbon material as a capacitor electrode material.

[0017] The present invention has the following beneficial effects:

[0018] (1) The prior art (such as 200510047800.X) usually uses a direct current arc method to convert biomass materials (such as coal liquefaction residue) into nano carbon fiber materials. Currently, there is no prior art for preparing porous carbon materials using a direct current arc method. The present invention first pre-treats poplar wood chips with arc discharge, which has a high reaction rate, controllable material morphology, and has a certain activation and expansion effect on the pore structure of the material. Then, high-temperature pyrolysis and carbonization are performed to obtain a poplar-based porous carbon material. Different from dispersed nano carbon fiber materials, the porous carbon material obtained by the present invention retains micropores on the basis of arc treatment, and at the same time realizes the transformation of some micropores to mesopores, thereby obtaining an ideal pore structure with coexistence of mesopores and micropores.

[0019] (2) The poplar-based porous carbon material prepared by the present invention is applied in the field of energy storage and exhibits excellent electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a cross-section SEM image of the poplar-based porous carbon material YC-D synthesized in Example 1.

[0021] Figure 2 This is the SEM image of the longitudinal section of the poplar-based porous carbon material YC-D synthesized in Example 1.

[0022] Figure 3 This is the Raman spectrum of the poplar-based porous carbon material YC-D synthesized in Example 1.

[0023] Figure 4 This is the nitrogen adsorption-desorption curve of the poplar-based porous carbon material YC-D synthesized in Example 1.

[0024] Figure 5 This is a constant current charge-discharge curve (GCD) of the poplar-based porous carbon material YC-D synthesized in Example 1.

[0025] Figure 6 This is a cross-section SEM image of the poplar-based porous carbon material YD-C synthesized in Example 2.

[0026] Figure 7 This is a SEM image of the longitudinal section of the poplar-based porous carbon material YD-C synthesized in Example 2.

[0027] Figure 8 This is the Raman spectrum of the poplar-based porous carbon material YD-C synthesized in Example 2.

[0028] Fig. 9 This is the nitrogen adsorption-desorption curve of the poplar-based porous carbon material YD-C synthesized in Example 2.

[0029] Fig.10This is a constant current charge-discharge curve (GCD) diagram of the poplar-based porous carbon material YD-C synthesized in Example 2.

[0030] Fig.11 This is the cycle performance diagram of the poplar-based porous carbon material YD-C synthesized in Example 2. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the contents described above.

[0032] Example 1

[0033] A method for preparing a poplar-based porous carbon material by carbonizing a solid raw material, specifically comprising the following steps:

[0034] (1) Dried poplar wood chips with a size of 2 × 2 × 0.2 cm were placed in a tubular furnace and calcined at 800 °C for 2 h under a nitrogen atmosphere. Finally, they were naturally cooled to room temperature to obtain carbonized wood chips (named YC).

[0035] (2) The carbonized wood chip YC obtained in step (1) is used as the anode material and placed in a copper pot, and a high-purity tungsten rod is used as the cathode. Both the positive and negative electrodes are placed inside the reaction chamber of the DC arc equipment.

[0036] (3) Before the experiment begins, evacuate and repeatedly purge the air in the reaction chamber. After the purge is complete, introduce working gas (argon) at a gas pressure of 80 kPa.

[0037] (4) Turn on the power supply and circulating cooling water system, set the initial current to 60 A, the working voltage to 30 V, adjust the inter-electrode distance to 1 mm, and the discharge current to 60 A to achieve arc carbonization of the poplar wood chips.

[0038] (5) After the reaction was completed, the carbonized arc wood chips, namely the poplar-based porous carbon material (named YC-D), were collected after a single argon passivation treatment for 6 h.

[0039] Figure 1 This is a cross-section SEM image of the poplar-based porous carbon material YC-D synthesized in Example 1. Figure 2 This is a SEM image of the vertical section of the poplar-based porous carbon material YC-D synthesized in Example 1. Figure 1 It can be seen that the material retains the macropore and micropore structure of poplar wood. Figure 2 It can be seen that the longitudinal section of the arc-treated YC-D is smooth and flat, with unobstructed pores and distinct pore diameters. In addition, there are more evenly distributed dense small holes on the vertical pore walls, indicating that the arc discharge treatment has successfully achieved "secondary pore creation" at the pits.

[0040] The Raman spectrum of this material is shown in Figure 3 As shown in the figure, it can be seen that at 1337 cm -1 and 1580 cm -1 There are two obvious characteristic peaks at these two locations, namely D peak (disordered and defective structure) and G peak (degree of graphitization). D / I G ) value can be used to indicate the degree of defects and disorder of carbon materials. D / I G The larger the value, the higher the degree of disorder. D / I G The value is 0.837, indicating that it has a low degree of graphitization. The nitrogen adsorption and desorption curve is shown in Figure 4 As shown in the figure, it can be seen that at the relative pressure P / P 0 When the relative pressure is <0.1, the nitrogen adsorption of wood-based carbon materials increases rapidly, indicating that the number of micropores is rich. When the relative pressure is >0.1, an obvious hysteresis loop appears, proving that there are mesopores inside the pore structure. That is, the prepared poplar-based porous carbon material YC-D has abundant micropores and less mesopores. The specific data are shown in Table 1.

[0041] In Example 1, the poplar wood chips are first calcined and then arc carbonized. The results show that DC arc treatment of poplar wood chips has a good effect, but due to the lack of further pore activation reaction, the performance improvement effect on the poplar-based porous carbon material is not obvious. When the poplar-based porous carbon material YC-D prepared in this example is used as an electrode material in a supercapacitor, its constant current charge and discharge curve is as shown in the figure. Figure 5 As shown in the figure, the GCD curve is a relatively symmetrical triangle shape, which verifies the double-layer energy storage mechanism of poplar-based carbon materials. -1 The charge and discharge time at this current density is only about 140 s, indicating its low conductivity and rate performance. In addition, its mass specific capacitance is 129 mF g -1 , the area specific capacitance is 10.63 mF cm -2 The results show that it has a lower specific capacitance, see Table 2 for details.

[0042] Table 1 Pore structure characteristics of poplar-based porous carbon-carbon materials

[0043]

[0044] Table 2 Mass specific capacitance and area specific capacitance of poplar-based porous carbon materials

[0045]

[0046] Example 2

[0047] A method for preparing a poplar-based porous carbon material by carbonizing a solid raw material, specifically comprising the following steps:

[0048] (1) A poplar wood chip with a size of 2×2×0.2 cm was fully soaked and placed in a copper pot as the anode material, and a high-purity tungsten rod was selected as the cathode; the positive and negative electrodes were placed vertically and centrally symmetrically in the reaction chamber of the DC arc device.

[0049] (2) Before the experiment officially started, the reaction chamber was evacuated and the air in the chamber was repeatedly purged. After the purging was completed, the working gas (high-purity argon) was introduced at a gas pressure of 80 kPa.

[0050] (3) Start the circulating cooling water system, turn on the power and start the arc. The initial current is set to 60 A, the working voltage is 30 V, the distance between the two electrodes is adjusted to 1 mm, and the discharge current is 60 A to achieve arc carbonization of the poplar wood chips.

[0051] (4) After the reaction was cooled, a single argon passivation treatment was carried out for 6 h, and the arc carbonized poplar wood chips were collected and named YD.

[0052] (5) The arc carbonized poplar wood chips prepared in step (4) were used as raw materials and carbonized at 800 °C for 120 min in a nitrogen atmosphere in a high-temperature tube furnace. The products were collected to obtain arc carbonized wood chips, i.e., poplar-based porous carbon materials (named YD-C).

[0053] Figure 6 This is a cross-section SEM image of the poplar-based porous carbon material YD-C synthesized in Example 2. Figure 7 This is a longitudinally cut SEM image of the poplar-based porous carbon material YD-C synthesized in Example 2. It can be seen that the structure of YD-C is loose and porous, and the pore distribution is uniform, and the pore size difference is not large, indicating that arc discharge pretreatment followed by high-temperature pyrolysis carbonization can effectively improve the pore formation effect.

[0054] The Raman spectrum of this material is shown in Figure 8 As shown in the figure, it can be seen that the arc carbonized wood chips obtained by arc treatment and high-temperature carbonization are poplar-based porous carbon materials YD-C. D / I G The value is 0.832, indicating that the graphitization degree of the material is high. The nitrogen adsorption and desorption curve is shown in Fig. 9 As shown in the figure, it can be seen that the curve grows slowly in the relative pressure range of 0.0-1.0, indicating that the material has micropores; a closed loop is formed in the relative pressure region of 0.4-1.0, and the closed loop region is more obvious than that in Example 1, indicating that mesopores exist. Therefore, the number of mesopores in the YD-C obtained in Example 2 is abundant, and it belongs to a pore structure with coexistence of mesopores and micropores. The specific data are shown in Table 3.

[0055] When the YD-C prepared in this embodiment is used as an electrode material in a supercapacitor, its constant current charge and discharge curve is as follows: Fig.10 As shown in the figure, the GCD curve of YD-C shows a well-symmetrical approximately triangular shape. -1 The charge and discharge time at the current density is as long as 75000 s, indicating that it has high conductivity and excellent rate performance. In addition, its mass specific capacitance is measured to be 82550.06 mF g -1 (i.e. 82.55 F g -1 ), the area specific capacitance is 6389.38 mF cm -2 , indicating that it has a higher specific capacitance, see Table 4 for details. Fig.11 This is the cycle performance diagram of the poplar-based porous carbon material YD-C. After 2000 long-cycle tests, the capacitance retention rate of this electrode material is 95.76%, indicating that it has excellent long-cycle stability.

[0056] Table 3 Pore structure characteristics of poplar-based porous carbon-carbon materials

[0057]

[0058] Table 4 Mass specific capacitance and area specific capacitance of poplar-based porous carbon materials

[0059]

[0060] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a poplar-based porous carbon material by carbonizing a solid raw material, characterized in that: The method comprises the following steps: (1) Pretreatment of poplar wood chips by direct current arc method: Poplar wood chips are used as anodes and high-purity tungsten rods are used as cathodes in a direct current arc device. After the reaction chamber of the arc device is in a vacuum state, an inert gas is filled in as a working gas, the power is turned on and the arc is started. After the reaction is completed, the power is turned off. After the temperature inside the reaction chamber cools to room temperature, a passivation gas is introduced for passivation treatment to obtain arc carbonized poplar wood chips. (2) High-temperature calcination: The arc carbonized poplar wood chips prepared in step (1) are placed in a tubular furnace for calcination to obtain a poplar-based porous carbon material.

2. The method for preparing a poplar-based porous carbon material by carbonizing a solid raw material according to claim 1, characterized in that: In step (1), the raw material poplar wood chips are first immersed in water for 1 to 5 hours, and then placed in a DC arc device as an anode.

3. The method for preparing a poplar-based porous carbon material by carbonizing a solid raw material according to claim 1, characterized in that: In step (1), the arc reaction conditions are: the distance between the two electrodes is 1-10 mm, the discharge current is 10-70 A, the arc discharge time is 5-40 s, the inert gas is high-purity argon, and the filling pressure is 40-80 KPa.

4. The method for preparing a poplar-based porous carbon material by carbonizing a solid raw material according to claim 1, characterized in that: In step (1), the passivation gas is a single high-purity argon gas, and the passivation time is 5 to 7 hours.

5. The method for preparing a poplar-based porous carbon material by carbonizing a solid raw material according to claim 1, characterized in that: In step (2), the calcination temperature is 800°C and the calcination time is 100-150 min.

Citation Information

Patent Citations

  • Plasma method for preparing nano carbon material using coal liquefied residue as raw material

    CN100365177C

  • A method for production of potash enriched biochar from waste biomass

    WO2017208250A1